THE DEVELOPMENT BOOK OF STORY BASED SUNDANESE CULTURE AS MEDIA ON INDONESIAN LANGUAGE WITH PANTUN MATERIAL IN IV CLASS ELEMENTARY SCHOOL - Makarim, Helwiyah; Holipah, Siti; Helmi, Helmi (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The Development Book of Story Based Sundanese Culture as Media on Indonesian Language with Pantun Material in IV Class, Elementary School. Djuanda Bogor University in 2017. This research is a Research and Development (R&D) which has a goal to know more a story of book based on Sundanese culture with learning method Indonesian language on pantun materials, another goal is to determine which one is the best of story book. The procedure of this research take a model of Borg and Gall theory, the development has five stages; find out the information, product plan, product development, validation product and evaluation of the product. To know quality of products is based on the learning aspect, materials, and looking with gift quetionnaires as a purpose to know the media developed worthy used or not as a learning media. The result of this a research are a book of story based on Sundanese culture used a learning method Indonesian language with pantun materials in class IV elementary school has good qualities based the material expert 43, maximum points from 50 with very good category. the media expert 68, maximum points from 75 with very good category. The teacher aroundÂ  124.33, maximum points from 125 with very good category. Peer reviewer around 111.33, maximum points from 125 with very good category. Testing 49,44, maximum points from 50 with very good category. Temporary testing 49, maximum points from 50 with very good category, so that this is a book of Sundanese story has good using for taking in learning media Indonesian language with pantun material in grade IV Elementary School.